Test procedures to assess somatosensory abnormalities in individuals with back pain: a systematic review of psychometric properties. (4th May 2018) - Alqarni, Abdullah Mohammad; Manlapaz, Donald; Baxter, David; Tumilty, Steve; Mani, Ramakrishnan
Abstract: Background: Identification of somatosensory abnormalities in patients with low back pain (LBP) is essential for targeted treatment strategies in an attempt to reduce or normalize altered sensory processing within the central nervous system. Several test procedures have been used to assess somatosensory abnormalities in patients with LBP, however, these test procedure should possess optimal psychometric properties (PMPs) to be used in clinical practice. Objectives: To systematically review the literature to evaluate the level of evidence for PMPs of test procedures administered to identify somatosensory abnormalities in individuals with LBP. Methods: A comprehensive electronic literature search was conducted in seven databases from inception to March 2016. The QAREL checklist and the COSMIN tool were used to assess methodological quality of the included studies. The level of evidence was determined based on the methodological quality of included studies and the quality of statistical measures of measurement properties. Results: Nineteen studies related to LBP were included. Studies demonstrated limited evidence for reliability and discriminative validity for cross-friction algometry in sub-acute LBP. Additionally, moderate evidence of reliability and strong evidence of discriminative validity exists for: electronic pressure algometer in chronic LBP, and a decline of conditioned pain modulation using the electronic pressure algometer (test stimulus) and a cold presser (conditioning stimulus) in acute and chronic LBP. Conclusions: This systematic review identified test procedures which demonstrated acceptable PMPs. Further research with adequate methodological quality and standardized protocols is recommended to investigate the predictive ability and responsiveness of test procedures to ensure their extended clinical utility.